2000
DOI: 10.1007/s004240000308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium hypertonicity on water permeability in the mammalian rectum: ultrastructural and molecular correlates

Abstract: Minute-by-minute net water fluxes (Jw) were measured across the isolated rectal epithelium in rats and rabbits. Five minutes after a serosal (but not mucosal) hypertonic challenge (plus 200 mosmol/l) a significant increase in the basal Jw was recorded in both species [deltaJw, microl min(-1) cm(-2): 0.40+/-0.06 (rats); 0.45+/-0.10 (rabbits)]. At the same time, most epithelial cells shrank markedly while the intercellular spaces were wide open (electron microscopy studies). In freeze-fracture studies multi-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The relative contribution of these three mechanisms to transepithelial water movement along the gastrointestinal tract is far from being elucidated. Special attention should be paid to the role of the AQPs, involved, as in other organs, in the rapid and substantial bidirectional movement of fluid given that eight different AQPs have recently been identified in the gastrointestinal tract of mammals (Frigeri et al, 1995; Koyama et al, 1999; Ramirez‐Lorca et al, 1999; Kierbel et al, 2000; Calamita et al, 2001a; Elkjaer et al, 2001; Hatakeyama et al, 2001; Tani et al, 2001; Parvin et al, 2002; Okada et al, 2003; Mobasheri et al, 2004). However, their topographical distribution, cellular localization, expression and functioning in the gastrointestinal tract have not yet been completely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of these three mechanisms to transepithelial water movement along the gastrointestinal tract is far from being elucidated. Special attention should be paid to the role of the AQPs, involved, as in other organs, in the rapid and substantial bidirectional movement of fluid given that eight different AQPs have recently been identified in the gastrointestinal tract of mammals (Frigeri et al, 1995; Koyama et al, 1999; Ramirez‐Lorca et al, 1999; Kierbel et al, 2000; Calamita et al, 2001a; Elkjaer et al, 2001; Hatakeyama et al, 2001; Tani et al, 2001; Parvin et al, 2002; Okada et al, 2003; Mobasheri et al, 2004). However, their topographical distribution, cellular localization, expression and functioning in the gastrointestinal tract have not yet been completely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of aquaporin 1 in colon epithelium is controversial; it has been localized to the apical epithelial membrane in human colon by Hasegawa et al (1994) and in Octodon degus colon by Gallardo et al (2002), but has been reported to be entirely absent from the epithelial membranes in rat colon (Nielsen et al 1993). In contrast to the apical membrane, the basolateral membrane of rat colonic and rectum surface epithelium expresses aquaporin 3 abundantly (Matsuzaki et al 1999, 2004; Kierbel et al 2000). It appears possible, therefore, that the apical (and also the basolateral) membranes of colon epithelium lack aquaporin 1, which is the only aquaporin isoform that has been associated with CO 2 transport.…”
mentioning
confidence: 99%
“…To elucidate the situation in the caecum, we investigated histamine and mannitol fl uxes in parallel. Mannitol is an established probe to determine paracellular permeability [33,34]. The positive correlation between histamine and mannitol fl ux rates in both fl ux directions (Fig.…”
Section: Discussionmentioning
confidence: 99%